Anlotinib added to third generation EGFR tyrosine kinase inhibitor therapy for advanced NSCLC patients with oligo-progression: a retrospective study (ALTER-L058) - Zhou, Fei; Zhuo, Minglei; Wang, Hongmin; Yang, Nong; Li, Jisheng; Jin, Shi; Han, Zhengxiang; Zeng, Guilin; Liu, Jun; Song, Yang; Wang, Kangwu; Huang, Dabing; et al. (Frontiers in Pharmacology, 2025)
ObjectiveTo investigate the efficacy of anlotinib, an antiangiogenic multikinase inhibitor, as an add-on therapy to first-line epidermal growth factor receptor (EGFR) tyrosine-kinase inhibitor (TKI) for patients with EGFR-mutant non-small cell lung cancer (NSCLC) who were previously untreated before first-line EGFR TKI but subsequently developed oligoprogression.MethodsThis multicenter, retrospective cohort study (ALTER-L058) analyzed data from the electronic health records-derived de-identified systems at 16 cancer centers in China. Adult patients between 18 and 75 years of age with histologically or cytologically confirmed locally advanced or metastatic NSCLC who received first-line third-generation EGFR TKI monotherapy and had an oligoprogressive disease were included. Eligible patients received anlotinib (8, 10 or 12 mg) on days 1–14 of each 3-week cycle for ≥6 cycles. Tumor response was assessed radiologically by investigators per RECIST, version 1.1. The primary outcome was investigators-assessed progression-free survival, calculated from the date of medication initiation for the oligoprogressive disease to the first documented progressive disease or death.ResultsBetween January 2020 and December 2023, 100 patients received EGFR TKI plus anlotinib and 50 received EGFR TKI. At the data cutoff (20 November 2024), the median progression-free survival was 9.23 months (95% CI, 8.94–10.87) with EGFR TKI plus anlotinib versus 5.42 months (95% CI, 4.83–6.80) with EGFR TKI (hazard ratio [HR] = 0.38, 95% CI, 0.26–0.56; log rank test, P < 0.0001), meeting the primary endpoint. Anlotinib was generally well tolerated, with manageable adverse events.ConclusionAnlotinib, when added onto EGFR TKI therapy following gradual progression or oligo-progression, conferred significant PFS benefits upon EGFR mutant NSCLC patients, supporting adding anlotinib to ongoing first-line EGFR TKI therapy for oligoprogressive disease.